The Antiviral Effects of Harmine Against BoHV-1 Infection In Vitro - Jiang, Xinyi; Zou, Jie; Zhuang, Yuncheng; Yuan, Weifeng; Zhu, Liqian; Zhu, Guoqiang (Letters in Drug Design & Discovery, 2017)
Introduction: The plants derived component harmine has various pharmacological activities such as antimicrobial, antifungal, antitumor. The antiviral effect of harmine on herpes simplex virus types 1 and 2 (HSV-1 and -2) has been well investigated, while whether it affects BoHV-1 infection is unknown. Objectives: The aim of the study is to investigate whether harmine affects BoHV-1 infection and the virus induced inflammation related signaling MAPK pathways. Methods: To assess the antiviral effect of harmine on BoHV-1 infection, MDBK cells were treated with harmine at different stages of virus infection, including through virus infection stages plus a pretreatment for 1 h, the virus entry stages, postentry stages and the virus binding stags. To evaluate whether the antiviral effects of harmine on BoHV-1 infection was enhanced by the known anti-herpesvirus drug acyclovir (ACV), both harmine and ACY at low concentrations that have minor effects on BoHV-1 infection were selected for combination used for the treatment of MDBK cells. The antiviral effect of the combined chemicals were compared with the application used individually. The effects of harmine on the activation of the inflammation related signaling MAPK pathways were also detected. Results: Here, for the first time we reveals that harmine affects BoHV-1 infection at both early and late stages of infection. The inhibitory effect was significantly enhanced by the known antiherpesvirus medicine ACV. While, it has no apparent effects on the activation of inflammation related signaling of neither p38MAPK nor Erk1/2 stimulated by BoHV-1 infection. Conclusion: Harmine inhibited BoHV-1 replication, in vitro, which could be synergistically enhanced by ACV. But harmine has no evident effect on the inflammation related signaling Erk1/2 and p38MAPK stimulated by BoHV-1 infection.
Keywords: harmine